(untitled) (Research, Society and Development, 2025)
Mozambique, and specifically the city of Beira, faces high vulnerability to floods and cyclones, exacerbated by its low coastal elevation and disorganized urban expansion into risk areas. This vulnerability is multidimensional. This study aimed to analyze the determining factors of the population’s permanence in Beira’s risk zones, despite the threat of recurrent disasters. A quantitative study was conducted, surveying 337 individuals in vulnerable neighborhoods. Structural Equation Modeling (SEM) was used to investigate the impact of economic, social/cultural, psychological, and structural factors on the intention to stay. SEM revealed that the main determinant of permanence is the social/cultural factor (β=0.978, p<0.001), confirming the direct influence of community ties and territorial identity. This single factor accounted for 89.7% of the variance in permanence. Conversely, economic, structural, and psychological factors were not direct predictors, but exhibited strong positive correlations among themselves, operating as an interdependent cluster. Permanence is primarily a decision of belonging and collective identity, rather than one of individual logic. Disaster risk reduction and resettlement policies must, therefore, prioritize the social and cultural factor, focusing on strategies that rebuild or maintain social networks in new locations to ensure intervention effectiveness.